Advances and applications of the fungal bioluminescence pathway - Yuhao Li; Dang Xu; Hao Du (Crop Design)
Bioluminescence has emerged as a valuable resource for developing novel biological tools and engineered luminescent organisms. The fungal bioluminescence pathway (FBP) represents a particularly promising system, employing endogenous, non-toxic substrates to enable sustained light emission in autoluminescent plants. Recent progress in substrate optimization, enzyme engineering, and metabolic pathway enhancement has significantly improved the system's robustness, facilitating commercial applications. Beyond plant illumination, FBP has proven effective as a biological reporter for quantitative measurements in research settings. This review comprehensively examines the FBP system, detailing its progress, challenges, and multidisciplinary applications. As an innovative biotechnology system, the FBP system paves the way for a future illuminated by living organisms.